Centrum handlowo-rozrywkowe jako 'miejsce' w przestrzeni społecznej Łodzi. Przykład 'Manufaktury' - Wójcik, Marcin (Space – Society – Economy, 2009)
The article presents the commercial and entertainment complex as a “place” in the social space of the city. “Manufaktura” is renewal, revitalized area in the inner city. This space is involved in the implementation of the consumption needs of residents of the city and is also an important element in the identification of social and territorial cohesion. Manufacture creates new forms of consumption, which make up a new dimension of social and cultural space of the city. The positive perception of the place by the people is connected with a combination of many functions here – trade, meeting place and process of provide the experiences. Processes of the functional and spatial transformation are strictly determined by the social phenomenon of the recovery history, and thus social identity. New public space and its specific physiognomy, clear and safe space, in the result give feeling of uniqueness and pride. The huge investment has created a big contrast to the neighboring deprived areas. Some of them which have historic value have lost these days the chances for renewal process.